Boosting soot combustion efficiencies over CuO–CeO2 catalysts with a 3DOM structure. Issue 19 (22nd August 2016) - Wang, Jinguo; Cheng, Li; An, Wei; Xu, Jingli; Men, Yong
Abstract : A CuO–CeO2 catalyst with a well-defined 3DOM structure exhibited superior catalytic activity for soot combustion compared to its 3DOM CeO2 counterpart. Abstract : Three-dimensionally ordered macroporous CuO–CeO2 catalysts were successfully synthesized by the colloidal crystal template route and systematically characterized by means of XRD, FESEM, HRTEM, BET, XPS, FTIR, H2 -TPR and O2 -TPD. The 3DOM CeO2 with a CuO loading amount of 9.7 wt% exhibited the optimal catalytic activity, giving a T m of 427 °C and an exceptionally high CO2 selectivity of nearly 100%. This superior activity was attributed to the enlarged contact area between the catalyst and soot particles, the improved mass transfer caused by the well-defined 3DOM structure and the enhanced redox capability at low temperatures mainly associated with the highly dispersed copper species. Meanwhile, the effect of feed compositions on soot combustion efficiencies revealed that NO and H2 O had a crucial promoting effect on the catalytic oxidation of soot particles because NO2 formed via in situ NO oxidation during the reaction and H2 O significantly reduced the activation energy of carbon. Furthermore, this catalyst also demonstrated strong durability against structural collapse owing to the well-defined and robust 3DOM structure, indicating its potential applications under practical working conditions.